Variations in the branching pattern of renal artery - Aishwarya Thanigai Arasu; Muniappan Veerappan; Sundarapandian Subramanian; Ananthi Varadharajan (Asian Journal of Medical Sciences, 2022)
Background: In terms of living kidney transplantation programs worldwide, India is only second to the United States of America. Every year, over 7500 renal transplants are done in India, with 90% of the transplants coming from living donors and the rest from deceased donors. Aims and Objectives: The aim of the study is to examine and describe differences in human renal arteries, compare past studies with the present study, and report the occurrence of major categories of variation. Materials and Methods: This observational study was carried out on 25 well-embalmed adult cadavers in the Department of Anatomy, Rajah Muthiah Medical College, Annamalai Nagar, Chidambaram from December 2016 to October 2018. In all the 25 specimens, the renal artery took its origin from the lateral side of the abdominal aorta. Results: We observed that there is a 92% correlation between L1 and L2, 8% between L3 and L1, and zero between L1 and L2. Accessory renal artery (ARA) was discovered in 18 specimens (36%), with 10 on the right side and eight on the left. Superior polar arteries – 4 (8%), inferior polar arteries – 1 (2%), and hilar arteries – 5% on the right side (10%). Superior polar arteries – 6%, inferior polar arteries – 0%, and hilar arteries – 5% on the left side (10%). Conclusion: Living donor grafts have become a primary source for preserving the donor pool as the need for kidney transplantation rises, and a successful allograft with numerous arteries has become a must. All major vascular channels have not entirely regressed if there are polar or numerous renal arteries to a regularly positioned kidney.